Effect of wire electric discharge machining (EDM) parameters on fatigue life of Ti-6Al-4V alloy. (November 2019) - Pramanik, A.; Basak, A.K.
Highlights: S – N curves for samples machined at different conditions are presented. Fatigue performance is very similar for all samples at higher cyclic loading. Contributions of machining conditions were noted at lower cyclic loading. Fatigue cracks initiated from the both sides of the samples. Surface roughness and feed did not contribute to fatigue performance. Recast layer and heat affected zone are the main contributor to the fatigue performance. Abstract: The effect of pulse on time, pulse off time and wire tension were investigated on the fatigue life, crack propagation, surface roughness and machining feed during wire EDM of Ti-6Al-4V alloy. The fatigue performance of all samples is very similar at higher cyclic loading. The machining conditions affected the lower cyclic loading. Lower pulse-on time and higher pulse-off time gave the longest life at lower cyclic loading. The higher wire tension gave shorter life and then remained almost constant at lower tension. It seems that the recast layer and heat affected zone are the main contributor to the fatigue performance.